Putusan Sela Perkara Perdata Bila Penggugat Asal Meninggal Dunia - I Kadek Agus Widiastika Adiputra; I Nyoman Gede Sugiartha; I Made Minggu Widyantara (Jurnal Preferensi Hukum, 2021)
The decision of the Panel of Judges on Civil Case No. 414/Pdt.G/2019/PN Dps, which continued the trial and set an interim decision even though one of the plaintiffs had died, contradicted the Jurisprudence of the Supreme Court of the Republic of Indonesia Number 431K/Sip/1973, dated May 9, 1974. This study aimed to examine the setting of interlocutory decisions on the civil procedural law and examine the judge's considerations in determining the continuation of the trial process in the case of decision Number: 414/Pdt.G/2019/PN Dps when the original plaintiff died. This research was designed by using normative legal research and legislation approaches. The data used were primary and secondary legal data collected through documentation techniques by processing and analyzing legal literature that had been collected using legal arguments. The results of the study indicated that the provision of interlocutory decisions was regulated in Article 185 HIR/196 RBg. Interlocutory decisions could be divided into 4 groups, namely preparatory, interlocutor, incidental, and provisional. The judges' considerations in civil cases Number: 414/Pdt.G/2019/PN Dps The Intervenient asked the Panel of Judges to be given the position of a Plaintiff-Intervenor based on the legal basis of disputes over property rights, over the land and buildings on it with the Intervenient's position as a buyer in good faith.